Neophenomenology or the new french phenomenology - Wilkołek, Rafał (Filozofia Chrześcijańska, 2024)
The article outlines the development of the philosophical movement known as the “theological turn of French phenomenology”. The first part describes the origins of this group of thinkers related to Dominique Janicaud’s “founding” accusations against the phenomenological works of Michel Henry, Jean-Luc Marion and Jean-Louis Chrétien, among others. The second part deals with the systematizing consciousness responses from both the authors of the so-called “turn”, as well as current comments by Janicaud and the French theological community. The third part of the article describes the reactions of philosophical historians outside of France, who have expanded the spectrum of views of the henceforth so-called “new phenomenology” to include its radicalized forms. The conclusion shows the possible application paths of the present systematization to the field of parallel phenomenological activity created by other authors who have not yet been recognized as forming the described movement of thought.